Content Validation and Internal Consistency of a Questionnaire about Entering the Workforce from the University Student’s Perception - Martínez Clares, Pilar; González Lorente, Cristina (Revista Complutense de Educación, 2017)
In the current context of crisis and social and labor instability, it seems inescapable to delve into the factors and psychosocial variables that university students face and how they can act as determinants or conditions in the job search as well as the intrinsic quality of entering the workforce as graduates. Along these lines, the aim of this paper is to validate an ad hoc questionnaire focused on entering the workforce for university students to know and analyze the main participant aspects in this process. In total, 931 final year students have participated from University of Murcia and University of Granada. To gather information and analyze data, a mix methodology has been used to obtain evidences of the content and the construct of this questionnaire in one single process. The main results show a unison agreement among the evaluators and a high rate of reliability in the different scales included in the questionnaire. These results are an interesting contribution in the scientific and psychometric field to promote investigations which are focused on the complex process of the entering the job market as university students and their employability.